ANALISIS TENTANG FAKTOR PENGHAMBAT DAN PENDUKUNG PARTISIPASI POLITIK ETNIS MELAYU DAN TIONGHOA DI KELURAHAN TANJUNG PINANG TIMUR KECAMATAN BUKIT BESTARI PROVINSI KEPULAUAN RIAU - Kajura Nopiza; Sri Erlinda; Zahirman ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was motivated by the many people who are less actively participate in activities of political participation. The research problems are whether the inhibiting and supporting factors of the Malay ethnic political participation in Tanjung Pinang east village Bukit Bestari District of Kepulauan Riau province and whether the inhibiting and supporting factors of the Chinese ethnic political participation in Tanjung Pinang Bukit Bestari Eastern District of kepulauan Riau province.This study aimed to determine what are the inhibiting factors and supporting factors the political participation of Malays ethnic in Tanjung Pinang Bukit Bestari Eastern District of kepulauan Riau Province and What are inhibiting factors and supporting factors the political participation of Chinese ethnic in Tanjung Pinang Bukit Bestari Eastern District of Riau Islands province. By using purposive sampling technique was obtained 80 people as a community sample of this research. The Data collected through questionnaire and interview.The results of the research showed the inhibiting factors Political Participation of Malays ethnic in Tanjung Pinang East was found 46.67% are answered yes and 53.33% are answered no whereas the Supporting factors Political Participation of Malays ethnic in Tanjung Pinang East was found 61.04% are answered yes and 38.96% are answered no. After that, the Inhibiting Factors Political Participation of Chinese ethnic in Tanjung Pinang East was found 51.46% are answered yes and 48.54% are answered no whereas the Supporting factors Chinese ethnic Political Participation in Tanjung Pinang East was found 60.84% are answered yes and 39.16% are answered no. Based on the results from overall recapitulation was obtained the average amount of each recapitulation percentage is 55% said Yes and 45% said No.Keywords: Political Participation, Malay, Chinese